Legal Protection for Victims of Defamation by Journalists - Anshar, Muhammad Rafi Naufal; Ruslie, Ahmad Sholikhin (Activa Yuris: Jurnal Hukum, 2025)
Mass media in Indonesia plays a significant role in disseminating information and influencing society. Information can spread widely to various corners of the world and be accessed by millions of readers simultaneously. Journalists are prohibited from carrying out actions that harm other people, spreading false news or slander, or taking sides with the intention of inciting. Legal protection for victims of defamation is necessary to maintain a balance between press freedom and individual rights. The problem in this research is how is the legal protection for victims of defamation committed by journalists? This type of research is normative research with a statutory approach and a conceptual approach. The technique for collecting legal materials is carried out through searching and collecting legal materials, researching legal issues, as well as case studies from statutory regulations, legal journals, literature books, news and other materials relevant to the research topic. The results of this research show changes in the rules for defamation by journalists in the old and new Criminal Codes, reflecting a firmer response to the challenges of the digital era and the protection of individual rights. Article 310 of the old Criminal Code provides light sanctions while Article 433 of the 2022 RKUHP provides heavier sanctions and detailed regulations. The main focus is legal protection for victims in the era of social media with the Indonesian Journalist Code of Ethics (KEWI) as a guide. The importance of the Press Law as a lex specialis ensures a balance between press freedom and the protection of individuals who are disadvantaged.